2021
DOI: 10.1371/journal.pone.0255379
|View full text |Cite
|
Sign up to set email alerts
|

Hematological abnormalities and comorbidities are associated with COVID-19 severity among hospitalized patients: Experience from Bangladesh

Abstract: Background The hematological abnormalities are assumed to be involved in the disease progression of COVID-19. However, the actual associations between specific blood parameters and COVID-19 are not well understood. Here we aimed to assess the correlations between hematological parameters and the severity of COVID-19. Methods We included COVID-19 patients who were admitted to Evercare Hospital Ltd, Dhaka, Bangladesh, between November 10, 2020, to April 12, 2021, with a confirmed case of RT-PCR test. We record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 81 publications
10
73
1
Order By: Relevance
“…Several previous studies have shown that elderly patients and those with elevated D-dimer with multiple systemic comorbidities had severe COVID-19 infection [15,21,22]. In our study, diabetes mellitus, acute kidney injury on admission, and raised D-dimer levels were associated with severe infection.…”
Section: Discussionsupporting
confidence: 58%
“…Several previous studies have shown that elderly patients and those with elevated D-dimer with multiple systemic comorbidities had severe COVID-19 infection [15,21,22]. In our study, diabetes mellitus, acute kidney injury on admission, and raised D-dimer levels were associated with severe infection.…”
Section: Discussionsupporting
confidence: 58%
“… 1 - 17 The association of worse outcomes with the variables accounted for by the JRSS makes sense from a pathogenicity and literature standpoint. 1 - 17 The variables accounted for have either been reported as risk factors in multiple prior studies or involve an organ system that would be directly affected by the SARS-CoV-2 infection. 1 - 17 One of the risk factors, ethnicity, may be a marker of worse prognosis due to its very strong and well documented non-biological association with social and health inequalities or discrimination within society at large.…”
Section: Discussionmentioning
confidence: 99%
“…Among 12,924,116 (99.9%) persons whose age was known, 55.0% were aged ≥50 years, 16.8% were aged 40–49 years, and 28.2.% were aged 18–39 years. 24,25 One study reported that information about the vaccine, social influences, and trust in the healthcare profession significantly influence people to vaccinate. 26,27 There is no question that the current COVID-19 vaccines are effective and safe.…”
Section: Discussionmentioning
confidence: 99%